Persepsi Guru Pamong Terhadap Penguasaan Materi Pembelajaran Mahasiswa Praktek Lapangan Kependidikan (PLK) (Studi Terhadap Mahasiswa Sejarah FIS UNP Periode Semester Genap Tahun Ajaran 2020-2021) - Santi Anggrini; Zafri Zafri (Jurnal Kronologi, 2021)
This research is motivated by the lack of ability to master the learning materials of history students in carrying out PLK class 2017. This study aims to describe how the civil servant teacher's perception of mastery of learning materials for students in the educational field practice (PLK) Department of History, FIS UNP, in the even semester of the 2020-2021 academic year. This type of research is descriptive quantitative with data collection techniques using a questionnaire consisting of 6 indicators and 23 items. The subject of this research is a civil servant teacher from PLK students majoring in history at a high school in the city of Padang, totaling 13 people. The data analysis used was TCR analysis technique. Based on the results of the study, it turned out that most of the civil servant teachers' perceptions of the mastery of PLK student history learning materials were positive with a TCR of 64%. The civil servant teacher's perception of mastery of the material is not good related to teaching material, giving examples of historical material concepts. Explaining the structure of changes in historical material, less skilled when teaching in the classroom and less learning from various sources.